Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης σχετικά με την χορήγηση βοηθήματος για τους άπορους
Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης σχετικά με την χορήγηση βοηθήματος για τους άπορους